Performance investigation of bandgap, gate material work function and gate dielectric engineered TFET with device reliability improvement - Raad, Bhagwan Ram; Nigam, Kaushal; Sharma, Dheeraj; Kondekar, P.N. (Superlattices and microstructures, 2016)
This script features a study of bandgap, gate material work function and gate dielectric engineering for enhancement of DC and Analog/RF performance, reduction in the hot carriers effect (HCEs) and drain induced barrier lowering (DIBL) for better device reliability. In this concern, the use of band gap and gate material work function engineering improves the device performance in terms of the ON-state current and suppressed ambipolar behaviour with maintaining the low OFF-state current. With these advantages, the use of gate material work function engineering imposes restriction on the high frequency performance due to increment in the parasitic capacitances and also introduces the hot carrier effects. Hence, the gate dielectric engineering with bandgap and gate material work function engineering are used in this paper to overcome the cons of the gate material work function engineering by obtaining a superior performance in terms of the current driving capability, ambipolar conduction, HCEs, DIBL and high frequency parameters of the device for ultra-low power applications. Finally, the optimization of length for different work function is performed to get the best out of this. •Bandgap engineering improves ON-state current and suppresses the ambipolar behaviour.•Further, device performance is enhanced by work function engineering and gate dielectric engineering with bandgap engineering.•Optimization of the work function engineering is performed for improving device performance.